The effect of alprostadil on preventing contrast-induced nephropathy for percutaneous coronary intervention in diabetic patients: A systematic review and meta-analysis. Issue 46 (November 2016) - Ye, Ziliang; Lu, Haili; Guo, Wenqin; Dai, Weiran; Li, Hongqing; Yang, Huafeng; Li, Lang
Abstract: Background: At present, there are a lot of research about the effect of Alprostadil on preventing contrast-induced nephropathy for percutaneous coronary intervention (PCI) in diabetic patients, but the clinical efficacy is not consistent, so we conduct this study and therefore determine the dominant strategy for the treatment of PCI in diabetic patients based on the best evidence currently. Methods: An electronic database search was conducted in MEDLINE, Embase, Cochrane library, CBM, CNKI, VIP, and WanFang to retrieve randomized controlled trial (RCT) comparing Alprostadil versus hydration on preventing CIN for PCI in diabetic patients. Reference lists of relevant articles were also screened manually to retrieve additional ones. Two investigators independently assessed the eligibility of retrieved articles using predefined inclusion and exclusion criteria. All characteristics as well as outcome variables including incidence of CIN, blood urea nitrogen (BUN), cystatin C (CysC), glomerular filtration rate (GFR), serum creatinine (Scr), serum beta 2-microspheres (β2-MG) presented in each included study were extracted. Heterogeneity was thought to be significant when I 2 > 50%. All of the meta-analytic procedures were performed by using Review Manager software, version 5.3. Results: Finally, data from 8 articles including 969 patients were included into this meta-analysis, among them, 487 patients in the experience group, and 482 patients in the control group. Meta analysis showed that the incidence of CIN in the experimental group was significantly lower than that in the control group (OR = 0.28, 95%CI[0.18, 0.42]). The incidence of adverse reactions in the experimental group was significantly lower than that in the control group (OR = 0.46, 95%CI[0.24, 0.85]). The BUN of 24 hours, 48 hours, and 72 hours in the experimental group were significantly lower than that of control group (MD = –0.77, 95%CI [−1.22, –0.32]; MD = –1.38, 95%CI [−1.83, –0.92]; MD = –2.43, 95%CI [−2.68, –2.19], respectively). The CysC of 24 hours, 48 hours, and 72 hours in the experimental group were significantly lower than that of control group (MD = –0.30, 95%CI [−0.40, –0.21]; MD = –0.54, 95%CI [−0.68, –0.41]; MD = –0.49, 95%CI [−0.63, –0.35], respectively). The GFR of 24 hours, 48 hours, and 72 hours in the experimental group were significantly higher than that of control group (MD = 7.86, 95%CI [4.44, 11.29], MD = 18.23, 95%CI [13.76, 22.69], MD = 12.81, 95%CI [8.51, 17.11], respectively). The Scr of 24 hours, 48 hours, and 72 hours in the experimental group were significantly lower than that of control group (MD = –9.09, 95%CI [−12.67, –5.51], MD = –19.14, 95%CI [−23.61, –14.66], MD = –6.50, 95%CI [−8.29, –4.71], respectively). The β2-MG of 24 hours, 48 hours, and 72 hours in the experimental group were significantly lower than that of control group (MD = –0.12, 95%CI [−0.27, 0.03], MD = –0.55, 95%CI [−0.71, –0.39], MD = –0.50, 95%CI [−0.60, –0.39], respectively). Conclusion: Our result suggested that comparing with conventional Hydration, Alprostadil can significantly reduce the incidence of CIN, adverse reaction, and protect renal function in PCI in diabetic patients. Due to the limitations of the quality and quantity of the articles, this conclusion still needs further research to confirm.